Heritability of symbiont density reveals distinct regulatory mechanisms in a tripartite symbiosis. Issue 7 (26th February 2016) - Parkinson, Jasmine F.; Gobin, Bruno; Hughes, William O. H.
Abstract: Beneficial eukaryotic–bacterial partnerships are integral to animal and plant evolution. Understanding the density regulation mechanisms behind bacterial symbiosis is essential to elucidating the functional balance between hosts and symbionts. Citrus mealybugs, Planococcus citri (Risso), present an excellent model system for investigating the mechanisms of symbiont density regulation. They contain two obligate nutritional symbionts, Moranella endobia, which resides inside Tremblaya princeps, which has been maternally transmitted for 100–200 million years. We investigate whether host genotype may influence symbiont density by crossing mealybugs from two inbred laboratory‐reared populations that differ substantially in their symbiont density to create hybrids. The density of the M. endobia symbiont in the hybrid hosts matched that of the maternal parent population, in keeping with density being determined either by the symbiont or the maternal genotype. However, the density of the T. princeps symbiont was influenced by the paternal host genotype. The greater dependency of T. princeps on its host may be due to its highly reduced genome. The decoupling of T. princeps and M. endobia densities, in spite of their intimate association, suggests that distinct regulatory mechanisms can be at work in symbiotic partnerships, even when they are obligate and mutualistic. Abstract : Understanding the density regulation mechanisms behind bacterial symbiosis is essential to elucidating the functional balance between hosts and symbionts. We investigate whether host or symbiont genotype may influence symbiont density by crossing hosts in a tripartite symbiosis. The two symbionts are decoupled in their density, suggesting that in spite of their intimate association, distinct regulatory mechanisms can be at work in symbiotic partnerships, even when they are obligate and mutualistic.